PENGEMBANGAN MEDIA PEMBELAJARAN INOVATIF BERBASIS GAME QUIZIZZ UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN BAHASA INDONESIA DI MADRASAH TSANAWIYAH - Syifa Khoerunnisa; Yoyo Zakaria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to develop an innovative game-based learning media, Quizizz, to improve students' understanding of Indonesian language at Islamic Junior High Schools (Madrasah Tsanawiyah), specifically the topic "Upholding Human Values through Dramatic Texts." The background of this study was the low level of student understanding of the material taught, caused by a lack of variety in learning media, less interactive teaching methods, and low student motivation. The research method used was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects were eighth-grade students of Islamic Junior High Schools (MTsN). The research instruments consisted of tests (pretest and posttest), validation sheets from material experts and media experts, and student response questionnaires. Data were analyzed using quantitative descriptive analysis and paired sample t-test statistical tests. The results of the study indicate that the Quizizz-based learning media developed met the criteria of "Very Good" based on validation by material experts and media experts. The results of the Paired Sample t-Test showed a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest scores. The average student score increased from moderate to high after using the media. Student responses to the media achieved a percentage score above 80%, falling into the "Very Good" category. The conclusion of this study is that the Quizizz-based learning media is effective for improving student understanding of drama texts. This media can be an innovative alternative for teachers in delivering material in a more interactive, engaging manner, and in line with developments in educational technology.